Przedmiotowy zakres stosowania regresu ubezpieczeniowego w systemie ubezpieczeń gospodarczych - Sangowski, Tadeusz (Wydział Prawa i Administracji UAM, 1973)
The following article attempts to define the objective range of application of regress in the system of economic insurance based upon the analysis of regulation of regress in Polish and other countries' insurance systems and upon the insurance doctrine and practice. The determination of the range of application of indemnity principle in various types of insurance has been used as a starting point for the above mentioned analysis. The consequences resulting from using such principle have been reflected in the range of application of regress in these types of insurance. Regress, commonly used in the indemnity benefits, is not used as far as the non-indemnity benefits are concerned. Differences concerning the application of regress within a certain limited scope of personal insurance result, first of all, from the fact that the border-line between insurance compensating and non-compensating benefits is not always in agreement with the line dividing economic insurance into property and personal insurance. Varieties of legal regulation of regress in personal insurance result from different conceptions of the legal nature of certain types of personal insurance (particularly from personal injury) and from making them, consequently, fully or partly compensating. Taking into consideration the purpose of controversial personal insurance and the need of some legal medium (regress) which would fulfill, first of all, the socially-didactic functions in preventing accidents caused by third parties, the favourable attitude has been accepted towards the limited range of using regress as far as some personal compensating benefits are concerned.
The Objective Range of Application of Regress in the System of Economic Insurance